Cerebral malaria. Issue 4 (1st October 2000) - Newton, Charles R J C; Hien, Tran Tinh; White, Nicholas
Abstract : Cerebral malaria may be the most common non-traumatic encephalopathy in the world. The pathogenesis is heterogenous and the neurological complications are often part of a multisystem dysfunction. The clinical presentation and pathophysiology differs between adults and children. Recent studies have elucidated the molecular mechanisms of pathogenesis and raised possible interventions. Antimalarial drugs, however, remain the only intervention that unequivocally affects outcome, although increasing resistance to the established antimalarial drugs is of grave concern. Artemisinin derivatives have made an impact on treatment, but other drugs may be required. With appropriate antimalarial drugs, the prognosis of cerebral malaria often depends on the management of other complications—for example, renal failure and acidosis. Neurological sequelae are increasingly recognised, but further research on the pathogenesis of coma and neurological damage is required to develop other ancillary treatments.